Jurnal Pendidikan IPA Indonesia - H. Husamah (Prodi IPA Fak. MIPA UNNES dan PPII, 2015)
- Blended Project Based Learning : Thinking Skills of New Students of Biology Education Departemen (Enviromental Sustainability Perspective) - Skill of Teacher Candidates in Integrating the Concept of Science with Local Wisdom - Integrated Development of Chemical Teaching Materials on Material Based Thermochemical Soft Skills For Vocational Students - Development Assesment of Alternative Practicum II Basic Chemical Through Chemistry Fair Project (CPT) Based Conservation Using Chemical Daily - Increasing Teachers Inquiry Ability with Training Inquiry Programme And Teaching Science - Critical Thinking Skills And Creativity Enhancement in 7th Grade Students Through PBL Model And Jas Approach - Argument Skills Enhancement Through The Implementation of Problem Based Learning in 10th Grade Students of MIA 1 SMA Batik 2 Surakarta - Development Creative Thinking Skills And Creative Attitude Through Problem Based Green Vision Chemistry Environment Learning - Sounds Learning Using Tems Games Tournament With Flash Card As Media at the 13th Junior High School of Magelang